2022
DOI: 10.3390/en15197331
|View full text |Cite
|
Sign up to set email alerts
|

Study on Winter Comfort Temperature in Mixed Mode and HVAC Office Buildings in Japan

Abstract: Comfort temperature is important to investigate because the chosen office indoor temperatures affect the energy used in a building, and a thermally comfortable environment makes the occupants be more productive. The effects of temperature on comfort are broadly recognized for thermal comfort. Japanese office buildings are well equipped with air-conditioning systems to improve the thermal comfort of the occupants. The main objectives of this research were to compare the winter comfort temperature in mixed mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The tendency of males to prefer lower comfort temperatures than females in the CL mode is because males exhibit more environmental behavioral adjustments to experience coolness than females, as described below. According to a previous study performed in the Aichi prefecture of Japan in winter [25], the mean comfort temperature of males is 1.4 • C lower compared with that of females in heating, ventilation, and air conditioning (HVAC) building cases, although the comfort temperatures for the two genders were found to be almost the same (approximately equal to 25.0 • C) in MM building cases. Similarly to the aforementioned previous study [25], this study showed that the comfort temperatures for the two genders were almost the same in the FR and HT modes.…”
Section: Comfort Temperature Based On Gendermentioning
confidence: 88%
See 1 more Smart Citation
“…The tendency of males to prefer lower comfort temperatures than females in the CL mode is because males exhibit more environmental behavioral adjustments to experience coolness than females, as described below. According to a previous study performed in the Aichi prefecture of Japan in winter [25], the mean comfort temperature of males is 1.4 • C lower compared with that of females in heating, ventilation, and air conditioning (HVAC) building cases, although the comfort temperatures for the two genders were found to be almost the same (approximately equal to 25.0 • C) in MM building cases. Similarly to the aforementioned previous study [25], this study showed that the comfort temperatures for the two genders were almost the same in the FR and HT modes.…”
Section: Comfort Temperature Based On Gendermentioning
confidence: 88%
“…Table 2 [8,15,[21][22][23][24][25][26] lists the outdoor, indoor, and comfort temperatures of office buildings obtained from different field studies conducted in Japan. First, a study on offices in the Kanto region found that the comfort temperatures ranged from 24.3 to 25.4 • C in the following three modes: FR, cooling (CL), and heating (HT) modes [23].…”
Section: Introductionmentioning
confidence: 99%
“…The chosen office buildings were of change-over mixedmode type having operable door/windows and the HVAC systems depending on the seasons or the time of the day. Detailed information about the office buildings is further elaborated in Khadka et al [13].…”
Section: Field Investigationmentioning
confidence: 99%
“…where h f donates resistance loss along the pipeline; λ presents resistance coefficient along the pipeline; L 1 , D, L 2 and d represent the length of the pipeline (10 m), pipe diameter (0.2 m), length of heat storage tube (0.3 m) and diameter of the TES tube (0.02 m), respectively; and n accounts for the number of accumulator tubes (10). Pipeline resistance coefficient λ:…”
Section: Operating Costmentioning
confidence: 99%
“…In terms of building energy consumption, heating energy accounts for approximately a quarter of the total in China's northern cities. Given the close relationship between heating and people's production and daily lives, the demand for clean heating has increased significantly, aiming to enhance indoor thermal environment quality and address climaterelated challenges [8][9][10]. Consequently, heating methods have become cleaner and more diversified, with the gradual adoption of approaches such as solar heating, geothermal heating, and electric heating.…”
Section: Introductionmentioning
confidence: 99%